2001
DOI: 10.1046/j.1471-4159.2001.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor mediates an excitoprotective effect of dietary restriction in mice

Abstract: Dietary restriction (DR; reduced calorie intake) increases the lifespan of rodents and increases their resistance to cancer, diabetes and other age-related diseases. DR also exerts beneficial effects on the brain including enhanced learning and memory and increased resistance of neurons to excitotoxic, oxidative and metabolic insults. The mechanisms underlying the effects of DR on neuronal plasticity and survival are unknown. In the present study we show that levels of brain-derived neurotrophic factor (BDNF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 70 publications
4
96
0
Order By: Relevance
“…When the excitotoxin kainic acid (KA) is injected into the dorsal hippocampus of mice it induces seizures and damage to pyramidal neurons in regions CA3 and CA1 (14). KA was injected into the dorsal hippocampus of mice that had been maintained for 24 weeks on AL, LDF, and IF diets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the excitotoxin kainic acid (KA) is injected into the dorsal hippocampus of mice it induces seizures and damage to pyramidal neurons in regions CA3 and CA1 (14). KA was injected into the dorsal hippocampus of mice that had been maintained for 24 weeks on AL, LDF, and IF diets.…”
Section: Resultsmentioning
confidence: 99%
“…Kainate was injected stereotaxically into the dorsal aspect of the right hippocampus by using the methods described (14). Briefly, mice were anesthetized with Avertin and placed in a stereotaxic head holder, and the skull was exposed along the midline.…”
Section: Excitotoxin Administration and Quantification Of Neuron Damagementioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this hypothesis, it has been reported that a brief period of FR after spinal chord injury is not associated with cortical or spinal chord enhancement of BDNF 45 . In all works showing an increase in BDNF signalling after FR, either adult animals restricted for 3 months or aged mice maintained under dietary regimen for their whole life were used [46][47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Both resveratrol and environmental enrichment have also been reported to extend lifespan and improve motor function in drosophila and rat models of Parkinson's disease, respectively, by activating sirtuins gene [15,38]. Caloric restriction and EE have been found to attenuate age-related deficits in learning and memory [15,39] and increase resistance of neurons to excitotoxic, oxidative, and metabolic insults and improve behavioural outcomes in experimental models of Alzheimer's and Huntington's disease [40]. The result obtained from this study using the elevated plus maze for memory, though not statistically significant, showed a slight decrease ( > 0.05) in the transfer latency (retention) across the groups when compared to the control with the least mean value obtained in the EE group.…”
Section: Discussionmentioning
confidence: 99%